The Role of Islamic Investment Ethics in Preventing Fraudulent Investments - Azhar Alam; Sri Herianingrum; Muhamad Nafik Hadi Ryandono; Nur Puji Rohmawati (Perbanas Journal of Islamic Economics and Business, 2023)
The case of bulging investment is still rife and causes losses for investors. This study aims to determine the role of Islamic investment ethics in preventing investment based on theoretical studies through a literature review and reinforced by the opinions of religious experts, investment experts, and law enforcement staff. This study used a descriptive qualitative approach using primary data from theoretical studies from various literature sources and interviews with ten people, including religious and investment experts. Moreover, The results show that the role of Islamic investment ethics in preventing investments such as staying away from riba, gharar, and maysir, using the principle "Al-Ghunm bi Al-Ghurm," which means the profit or income obtained is balanced with the losses incurred and uses the principle of prudence in making investments. This study provides advice on the need for education for the community related to investments related to riba, gharar, maysir, and the harmony between risk and profit, and the need for the principle of prudence before making investments that there is no case of bulging investment.